Treatment of delayed cervical oesophageal perforation with T-tube - Yu, Kah Ling; Diong, Nguk Chai; Sathiamurthy, Narasimman (International Surgery Journal, 2022)
Cervical oesophageal perforation is a potentially life-threatening situation associated with pooled mortality of 5.9%. Early detection and referral to the thoracic surgery is important. We present a case of an obese lady admitted for foreign body ingestion and had an endoscopic removal of foreign body. Her general condition deteriorated two days later and the diagnosis of delayed cervical oesophageal perforation was made. She was managed surgically by placement of T-tube as controlled-fistula, nasogastric tube insertion and drain at superior mediastinum to control sepsis and contamination. Patient was discharged well despite prolonged hospital stay. T-tube drainage is established as safe and effective to manage delayed cervical oesophageal perforation.